VD_FINDINFO AA 93/08 - 32/2010 vom 1. März 2010 - VD Tribunal cantonal (2010)
ACCIDENT, CAUSALITÉ NATURELLE, RECHUTE, SUITE D'UN ACCIDENT, OBJET DU LITIGE | 10 LAA, 16 LAA, 19 LAA, 6 al. 1 LAA, 11 OLAA